A Guide to School Self-Evaluation. Technical Report 4. Technical Report Series - Dekkers, John.; Western Australian Inst. of Technology, Bentley. Science and Mathematics Education Centre ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
This guide is designed primarily for administrators/teachers to provide: an introduction to the nature and purpose of school evaluation; an approach involving evaluation of issues determined by school staff; a set of procedures to carry out the evaluation; and guidance information and instruments for conducting an evaluation. Although the guide is designed primarily for school use, it is also useful for school superintendents, school advisors, and evaluators in their deliberations on the selection and assessment of an appropriate procedure for school evaluation from among those currently in use, for pre-/in-service teacher education programs or workshops as a basis for description and discussion of school evaluation procedures, and for parents and community members involved in the evaluation process. Key areas emphasized in the body of the guide are: purpose of school evaluation; identification of issues/areas to be evaluated; determination of level(s) at which evaluation should take place; key questions which serve as criteria for issues under evaluation; and steps to be followed in the evaluation process. Appendices include a handout on the purpose of school evaluation, sample minutes of a school evaluation committee meeting, sample evaluation time line, steps in using nominal group technique for clarifying goals, evaluation instruments, sample evaluation report, and bibliography. (JN)
Practitioners.
Community.
Parents.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Evaluation; Discipline; Elementary Secondary Education; Evaluation Criteria; Evaluation Methods; Evaluation Needs; Evaluators; Foreign Countries; Higher Education; Parent Participation; Program Evaluation; Questionnaires; School Effectiveness; Science Education; Self Evaluation (Groups); Student Attitudes; Teacher Attitudes; Australia (Western Australia); Guides, Non-Classroom.